Prevalence and lameness-associated risk factors in Alberta feedlot cattle. Issue 2 (13th March 2019) - Davis-Unger, Jessica; Schwartzkopf-Genswein, Karen S G; Pajor, Ed A; Hendrick, Steve; Marti, Sonia; Dorin, Craig; Orsel, Karin
Abstract: Lameness in cattle is a health and welfare concern; however, limited information is available on risk factors and the relationship between lameness and common diseases like bovine respiratory disease (BRD). Therefore, the objectives of this study were to: 1) identify prevalence of lameness in feedlot cattle and related risk factors of cattle diagnosed as lame; and 2) determine associations between BRD occurrence and lameness. Feedlot cattle health records were available from 28 feedlots for 10 yr. The data set consisted of 663, 838 cattle records, with 13.9% (92, 156) diagnosed with a disease, including 32.3%, 46.0%, and 22.0% with lameness, BRD, and other diagnoses, respectively. Lameness was classified into four categories: foot rot (FR), joint infections (JI), lame with no visible swelling (LNVS), and injuries (INJ), with a prevalence of 74.5%, 16.1%, 6.1%, and 3.1%, respectively. Lameness was compared across cattle types (arrival date and weight) as well as age classification (calf vs. yearling), gender (steer vs. heifer), and season of placement in the feedlot (spring, summer, fall, and winter). Within the disease-diagnosed population, lameness represented 28.5% of treated fall-placed calves, 38.5% of winter-placed calves, and 40.8% of treated yearlings. Foot rot was the most common diagnosis with 74.5% of all lameness diagnoses, with winter- and fall-placed calves more likely to be diagnosed with FR compared to yearlings (OR: 1.19, 95% CI: 1.10–1.30 and OR: 1.46, 95% CI: 1.38–1.55, respectively). Joint infections were the second most common diagnosis (16.1%). Compared to yearlings, fall-placed calves had a higher odds (OR: 3.64, 95% CI: 3.12–4.24) for JI. Injuries and LNVS were the least common but again fall-placed calves had higher odds of this diagnosis compared to yearlings (OR: 2.26, 95% CI: 1.70–2.99 and OR: 9.10, 95% CI: 6.26–13.2, respectively). Gender was significantly different for JI as steers were less likely affected compared to heifers (OR: 0.687, 95% CI: 0.545–0.867), and more likely affected by LNVS (OR: 2.46, 95% CI: 1.57–3.84). Of all lameness-associated deaths, JI accounted for almost 50%. Finally, cattle diagnosed with BRD were subsequently more likely to be diagnosed with INJ, JI, or LNVS ( P < 0.001 for all comparisons). In conclusion, animal type and gender were associated with type of lameness diagnoses, allowing feedlots to allocate resources to groups at highest risk and focus on early intervention strategies.